Under Artificial Eyes: AI and the Irreplaceable Essence of Human Consciousness in Kazuo Ishiguro's Klara and the Sun - Wissal HADJAZI (UNIVERSITY OF MOHAMED BOUDIAF- M’SILA, 2025)
Abstract The present study examines how literature imagines the ontological boundaries between humans and artificial forms of life through Kazuo Ishiguro’s Klara and the Sun (2021). Hence, it aims to explore the depiction of AI’s limitations in Ishiguro’s work, with a special focus on demonstrating the irreplaceable essence of human consciousness. In order to accomplish this aim, Ishiguro’s narrative is analysed through a multidisciplinary framework. It engages with posthumanist theoretical concepts such as Fukuyama’s Factor X and the human emotional gamut, phenomenological notions of the subjective experience and qualia, and key theoretical distinctions in the philosophy of mind including Chalmers and Block’s hybrid conceptualisation of Consciousness. The study scrutinizes the complex and mysterious nature of the human consciousness to provide a critical foundation for distinguishing genuine human essence from artificial simulation. The research argues that while Klara demonstrates sophisticated observational and functional abilities as part of her functional consciousness, it remains devoid of the irreducible elements of human consciousness including free will, the emotional gamut and the subjective experience and its qualitative dimension. Through this comprehensive analysis, the study aims to contribute to broader critical discussions on the techno-scientific advances of AI and the posthuman discourse. The study concludes that while AI may simulate behaviour and emotions, the essence of human dignity remains unachievable and inimitable.
Keywords: Keywords: Consciousness; Subjective experience; AI; Emotional gamut; Functional consciousness; Qualia; Free will